Effects of social media advertisements on intention to purchase health and beauty products / Hasman Abdul Manan …[et al.] - Abdul Manan, Hasman; Ariffin, Shahira; Ratul Maknu, Tengku Sharifeleani; Zakaria, Fatin Nabilah (Universiti Teknologi MARA Shah Alam, 2020)
Social media has become a necessity in nearly everyone's life today as it offers them the opportunity to keep in touch with family and friends. Social media is also acting as a medium for consumers to review or get an opinion on certain products before purchasing them. Even though purchasing online is convenient, yet it still creates skeptical opinions towards certain elements. Many companies do not realize the importance of preserving the integrity and truthfulness when it comes to advertising. Not all social media advertisements or posts are real. Therefore, this study aims to examine customers' perceptions of social media advertisements and their intention to purchase health and beauty products. A six-section questionnaire with a 5-point Likert scale, from 1- strongly disagree to 5 -strongly agree, was created for the study. The snowball sampling was the preferred sampling method to acquire data from 180 respondents, and these data were analyzed using SPSS version 24. The analysis results indicated that all variables' items were between the range of 0.728 to 0.859, which denotes the existence of internal consistency. From the regression analysis findings, trust and affective have significant positive effects on purchase intention, whereas credibility and authenticity showed non-significant relationships. The study found trust and affective attitude have significant positive relationships with purchase intention of products on social media. Whereas, credibility and authenticity are found to have no significant relationship with purchase intention. Between trust and affective, trust is found to have strongest influence on consumer purchase intention.